SOME REFLECTIONS TOWARDS LANGUAGE LEARNING - Widodo Purwanto (Unipdu Jombang, 2010)
Widodo Purwanto SMPN 2 Gudo Jombang diglossiafbs@gmail.com Â Abstract Language is something that is essential for human life, including English. If the first language learned from childhood and obtained directly from the parents by nature, English is different. English is introduced when they learn at schools. The very common difference found is grammar problems. In this paper, the authors convey the things that relate to teaching English in Indonesia as a whole including grammar, standard language, teaching grammar, and the last is pragmatic in the context of learning English in Indonesia. Everything is analyzed and accompanied by a reflection based on empirical experience of the authors who are practitioners in teaching English. key words: language learning, reflectionÂ Abstrak Bahasa merupakan sesuatu yang sangat penting bagi kehidupan manusia, termasuk Bahasa Inggris. Jika bahasa pertama dipelajari sejak kanak-kanak dan didapat langsung dari kedua orangtuanya secara alamiah, berbeda dengan Bahasa Inggris.Â Bahasa Inggris dikenalkan saat mereka belajar di sekolah. Perbedaan yang sangat umum ditemukan adalah permasalahan tata bahasa. Dalam tulisan ini, penulis menyampaikan hal-hal yang berhubungan dengan pembelajaran bahasa Inggris di Indonesia secara menyeluruh. Diantaranya adalah mengenai bahasa, tata bahasa, bahasa baku, pengajaran tata bahasa, dan yang terakhir adalah pragmatis dalam konteks pembelajaran bahasa Inggris di Indonesia. Semuanya dianalisa dan disertai dengan refleksi berdasarkan pengalaman empiris penulis yang merupakan praktisi dalam pengajaran bahasa Inggris. kata kunci: pembelajaran bahasa, refleksi